The effect of hip-hop songs on fat burning through zumba exercise: Case study in “Mic Drop” by BTS as zumba accompaniment - Puput Meinis Narselina; Delya Putri Ananda (Interlude: Indonesian Journal of Music Research, Development, and Technology, 2022)
This essay examines the correlation between hip-hop music and Zumba, with a specific focus on how the tempo of the music affects calorie burning and the overall workout experience. The study used a qualitative approach to examine the impact of participating in Zumba sessions with hip-hop genre music, namely "Mic Drop" by BTS, on calorie expenditure and exercise enjoyment. This investigation is based on current literature and audio-visual content available on YouTube. The results demonstrate that integrating fast-paced hip-hop music into Zumba workouts can burn roughly 1,440 calories each week. It is consistent with prior studies showing the beneficial impact of fast- paced music on heart rate and perceived physical exertion. Additionally, the research emphasizes the significance of choosing songs with appropriate tempos, such as hip-hop, to improve the exercise experience and facilitate more effective calorie expenditure during Zumba sessions. Nevertheless, it emphasizes the necessity for additional research to comprehensively comprehend music's influence on physical performance and physiological reactions during exercise. This study enhances our comprehension of the impact of music tempo on exercise motivation and outcomes by incorporating knowledge from academic literature and audio-visual materials available on platforms such as YouTube. This study provides a basis for future research and highlights the potential of using fast-paced music in Zumba exercise to maximize the advantages of physical activity.